Farmakokinetika dan Bioavailability Senyawa Golongan Santon Revew Komprehensif - Meri Susanti (Jurnal Penelitian Farmasi Indonesia, 2019)
The use of herbs for treating various ailment dates back several centuries. Evidence-based verification of the efficacy of Herbal medicines is still frequently lacking. Of particular interest is the question of bioavailability to assess to what degree and how fast compounds are absorbed after administration of herbal. Of further interest is the elucidation of metabolic pathways, and the assessment of elimination routes and their kinetics. These data become an important issue to link data from pharmacological assays and clinical effects. A better understanding of the pharmacokinetics and bioavailability of phytopharmaceuticals can also help in designing rational dosage regimens. To provide provide a detailed picture on ADME parameters (absorption, distribution, metabolism, and excretion) of some xanthone active compound, this article reviews the pharmacokinetic profile of 7 xanthones bioactive compound from the year 2009 onward.